Blue lupin (Lupinus angustifolius L.) ‒ the results of varieties and accessions study according to adaptivity and a set of commercialbiological traits - P. A. Ageeva; N. A. Potchutina; O. M. Gromova; N. M. Zaytseva (Аграрная наука Евро-Северо-Востока, 2022)
Cultivation of grain legumes including blue lupin (Lupinus angustifolius L.) is an important reserve for increase of high protein feed production. The aim of the research is to find perspective blue lupin varieties and accessions according to yield, adaptivity, the duration of vegetation period and biochemical indices in south-western area of the Central part of Russia. In 2019-2021 six blue lupin varieties and four accessions developed in the All-Russian Lupin Scientific Research Institute have been tested in competitive variety trial (Vityas was standard variety). The trials were laid on sod-podzolic, loamy soil with the moderate fertility level. The average grain yield of varieties in the trial was 2.07 t/ha, of standard variety – 1.85 t/ha. The varieties Bryansky kormovoy, Uzkolistny 53 and accessions BSv 51-19, USN 53-236 and SBS 56-15 had the highest grain yield. Their grain productivity varied from 2.17 to 2.29 t/ha. Statistically significant increase to the standard was 0.32-0.44 t/ha. The accessions BSv 51-19 and USN 53-236 had the maximum grain yield by adaptivity coefficient of 110%. According to the green mass yield and adaptivity Bryansky kormovoy and new promising accessions SBS 56-15, USN 53-236 and BSv 51-19 have been noted: the increase to the standard according to the green mass yield was 5.0-7.0 t/ha, the adaptivity coefficient was 104-110%. By the duration of vegetation period (80-89 days) all varieties and accessions were included into the group of early-ripening. The new tall variety Belorozovy 144 had the longest vegetation period (89 days). According to the alkaloid content in the grain (0.031-0.063 %) all tested varieties and accessions were included into the low-alkaloid group. The varieties Smena, Uzkolistny 53 and the accession SBS 56-15 were characterized by stable low index (0.031-0.039 %). The content of raw protein in the seeds of tested varieties and accessions of blue lupin varied in the range of 32.0-33.8%. According to the set of positive traits, Bryansky kormovoy variety and accessions USN 53-236 and SBS 56-15 have been noted.